A delayed detached eddy simulation model with low Reynolds number correction for transitional swirling flow in a multi-inlet vortex nanoprecipitation reactor. (16th January 2019) - Liu, Zhenping; Hill, James C.; Fox, Rodney O.; Passalacqua, Alberto; Olsen, Michael G.
Highlights: A transitional delayed detached eddy simulation model was developed for use in microscale vortex reactors. Simulation results were compared to microscopic particle image velocimetry and laser induced fluorescence experiments. Excellent agreement was observed between simulation and experiment. The model accurately simulated both the laminar and turbulent flow regimes in the reactor. Abstract: The objective of the presented work is to verify a delayed detached eddy simulation (DDES) model for simulating transitional swirling flow in a micro-scale multi-inlet vortex reactor (MIVR). The DDES model is a k- ω based turbulence model with a low Reynolds number correction applied to the standard k- ω model such that the Reynolds-averaged Navier-Stokes (RANS) component of the DDES model is able to account for low Reynolds number flow. By limiting the dissipation rate in the k-equation, the large-eddy simulation (LES) part of the DDES model behaves similarly to a one-equation sub-grid model. The turbulent Reynolds number is redefined to represent both modeled and resolved turbulence level so that underestimation of the RANS length scale in the LES range can be reduced. Applying the DDES model to simulate both laminar and transitional flow in the micro-scale MIVR produces an accurate prediction of mean velocity and turbulent intensity compared with experimental data. It is demonstrated that the proposed DDES model is capable of simulating transitional flow in the complex geometry of the micro-scale MIVR. These simulation results also help to understand the flow and mixing patterns in the micro-scale MIVR and provide guidances to optimize the reactor for the application of producing functional nanoparticles.